Darren Aronofsky's Human nature. Book 1 - Aronofsky, Darren; Handel, Ari; Welch, Jeff (Human Nature, 2026)
From Academy Award-winning filmmaker Darren Aronofsky comes the first volume of his satirical sci-fi trilogy, Human Nature From the visionary minds behind Black Swan and The Whale, Darren Aronofsky and Ari Handel team up with writer Jeff Welch and acclaimed artist Martin Morazzo (Ice Cream Man) for Human Nature, a razor-sharp social-satire trilogy about ambition, power, and humanity's desperate quest for immortality. Meet Duke: once just an ordinary nobody, now an ego-driven billionaire chicken magnate with nearly limitless wealth and power. But even endless fortune has limits--and Duke is obsessed with breaking the final barrier: death itself. Can he buy the key to defy death, or has his unchecked ambition finally gone too far? Overflowing with twisted humor, surreal adventures, and dazzling visuals, Human Nature hurtles readers into a bizarre yet unsettlingly familiar future, confronting unimaginable obstacles at every turn. It's a gripping, audacious ride that only Aronofsky could conjure--one that races forward at breathtaking speed, promising even greater thrills as the trilogy unfolds.